Expression of the POTE gene family in human ovarian cancer. Issue 1 (December 2018) - Barger, Carter; Zhang, Wa; Sharma, Ashok; Chee, Linda; James, Smitha; Kufel, Christina; Miller, Austin; Meza, Jane; Drapkin, Ronny; Odunsi, Kunle; Klinkebiel, David; Karpf, Adam
Abstract ThePOTE family includes 14 genes in three phylogenetic groups. We determinedPOTE mRNA expression in normal tissues, epithelial ovarian and high-grade serous ovarian cancer (EOC, HGSC), and pan-cancer, and determined the relationship ofPOTE expression to ovarian cancer clinicopathology. Groups 1 & 2POTEs showed testis-specific expression in normal tissues, consistent with assignment as cancer-testis antigens (CTAs), while Group 3POTEs were expressed in several normal tissues, indicating they are not CTAs.Pan-POTE and individualPOTE s showed significantly elevated expression in EOC and HGSC compared to normal controls.Pan-POTE correlated with increased stage, grade, and the HGSC subtype. Select individualPOTEs showed increased expression in recurrent HGSC, andPOTEE specifically associated with reduced HGSC OS. Consistent with tumors, EOC cell lines had significantly elevatedPan-POTE compared to OSE and FTE cells. Notably, Group 1 & 2POTEs (POTEs A/B/B2/C/D ), Group 3POTE-actin genes (POTEs E/F/I/J/KP ), and other Group 3POTEs (POTEs G/H/M ) show within-group correlated expression, and pan-cancer analyses of tumors and cell lines confirmed this relationship. Based on their restricted expression in normal tissues and increased expression and association with poor prognosis in ovarian cancer, POTEs are potential oncogenes and therapeutic targets in this malignancy.